Changes in TCA cycle and TCA cycle-related metabolites in plasma upon citric acid administration in rats. Issue 12 (December 2021) - Hara, Yurie; Kume, Satoshi; Kataoka, Yosky; Watanabe, Nakamichi
Abstract: Recent studies have reported that plasma levels of tricarboxylic acid (TCA) cycle metabolites and TCA cycle-related metabolite change in patients with chronic fatigue syndrome (CFS) and in healthy humans after exercise. Exogenous dietary citric acid has been reported to alleviate fatigue during daily activities and after exercise. However, it is unknown whether dietary citric acid affects the plasma levels of these metabolites. Therefore, the present study aimed to investigate the effects of exogenously administered citric acid on TCA cycle metabolites and TCA cycle-related metabolites in plasma. Sprague-Dawley rats were divided into control and citric acid groups. We evaluated the effect of exogenous dietary citric acid on the plasma TCA cycle and TCA cycle-related metabolites by metabolome analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS). TCA cycle metabolites, including plasma citrate, cis-aconitate, and isocitrate, were significantly elevated after exogenous administration of citric acid. Anaplerotic amino acids, which are converted to TCA cycle metabolites, such as serine, glycine, tryptophan, lysine, leucine, histidine, glutamine, arginine, isoleucine, methionine, valine, and phenylalanine, also showed significantly elevated levels. Citric acid administration significantly increased the levels of initial TCA cycle metabolites in the plasma. This increase after administration of citric acid was shown to be opposite to the metabolic changes observed in patients with CFS. These results contribute novel insight into the fatigue alleviation mechanism of citric acid. Abstract : Citric acid; Fatigue; Tricarboxylic acid cycle; Amino acid; Anaplerotic substrates; Metabolome analysis.